2006
DOI: 10.1002/ejic.200600092
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assemblies with Honeycomb Structures by π‐π Stacking of Octahedral Metal Complexes of 1,12‐Diazaperylene

Abstract: Homoleptic NiII and FeII complexes of the “large‐surface” phenanthroline‐type ligand 1,12‐diazaperylene (dap), [Ni(dap)3](BF4)2 (1) and [Fe(dap)3](PF6)2 (2), respectively, were synthesized. In the crystal structure the complex cation [M(dap)3]2+ (M = Ni, Fe) exhibits C3 symmetry and interacts with three other cations by π‐π stacking. It forms a new metalla‐supramolecular assembly with a honeycomb structure containing nanochannels running parallel to the crystallographic c axis. Aggregation by π‐π stacking betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Figure 5 shows that the four (square) or the three (triangle) metal atoms are located in the same plane, the pyridine rings are perpendicular to this plane, and the twisting between the two tetrafluorobenzene moieties is approximately 50°. π-π interactions between the pyridine and the phenyl rings of the diphosphane are expected to occur since the reported distance for these interactions between two parallel planes is 3.3-3.8 Å 65 and, in our case, the calculated distances are about 3.4 Å for the square and 3.6 Å for the triangle.…”
Section: Resultsmentioning
confidence: 82%
“…Figure 5 shows that the four (square) or the three (triangle) metal atoms are located in the same plane, the pyridine rings are perpendicular to this plane, and the twisting between the two tetrafluorobenzene moieties is approximately 50°. π-π interactions between the pyridine and the phenyl rings of the diphosphane are expected to occur since the reported distance for these interactions between two parallel planes is 3.3-3.8 Å 65 and, in our case, the calculated distances are about 3.4 Å for the square and 3.6 Å for the triangle.…”
Section: Resultsmentioning
confidence: 82%
“…In the spectrum of [1](PF 6 ) 2 , the broad feature in the 300-400 nm region can be assigned to d π (Ru)Ǟπ* (py) metalto-ligand charge transfer (MLCT) transitions, [26] and the absorption bands in the 400-500 nm region to dape-centered π-π* transitions. [27] In the spectra of the two tape complexes [2](PF 6 ) 2 and [3](PF 6 ) 4 , the d π (Ru)Ǟπ* (py) MLCT transitions overlap with the tape-centered π-π* transitions in the 300-470 nm region. Well separated from the absorption bands described above, the MLCT absorption bands due to the d π (Ru)Ǟπ* (dape or tape) transitions are observed at particularly noticeable low energies.…”
Section: Electronic Spectra and Electrochemical Propertiesmentioning
confidence: 99%
“…With the results of this and earlier works, [8] we have shown that the dimensionality of the π-π stacking interactions between metal complexes of 1,12-diazaperylenes or 2,11-dialkylated 1,12-diazaperylenes is a function of the coordination geometry. Whereas homoleptic octahedral metal complexes of 1,12-diazaperylenes form a supramolecular 3D honeycomb structure, homoleptic tetrahedral complexes could form 1D columnar structures.…”
Section: Discussionmentioning
confidence: 85%
“…[8] It is well known that copper(I) complexes of 2,9-disubstituted 1,10-phenanthrolines are key building blocks in supramolecular chemistry and therefore they are found in molecular structures, like molecular racks, [9] nanoboxes, [10] knots, [11] nanogrids, [12] wheels [13] and catenanes. [14] .…”
Section: Introductionmentioning
confidence: 99%